2015
DOI: 10.29313/mimbar.v31i1.1106
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Organisasi Informal Menjaga Persistensi Pasar Tradisional di Kecamatan Padang Barat

Abstract: The focus ofthis study is to examine the Strategy Informa Organizations Maintaining Persistence of Traditional Markets. This is due tothe marketis animportant institution in economic institutions. In addition, the market serves to bring together the economic actors. The market also serves as an economicmeans of providing a barometer of the economy in the area of income generation. This study used a qualitative approach with descriptive type. Informants in this study is determined by means of intentional (purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Banyak studi tentang pasar telah dilakukan di Sumatera Barat, mulai dari konflik (Zusmelia & Firdaus, 2016a, Ariesta, 2014, dinamika dan penatakelolaannya (Zusmelia & Firdaus, 2015, 2016b, gender (Ariesta, 2014), persistensi (Fitlayeni, Marleni & Elvawati, 2015) hingga jaringannya (Firdaus, Ariesta, Rahayu, & Shalihin, 2019).…”
Section: Pendahuluanunclassified
“…Banyak studi tentang pasar telah dilakukan di Sumatera Barat, mulai dari konflik (Zusmelia & Firdaus, 2016a, Ariesta, 2014, dinamika dan penatakelolaannya (Zusmelia & Firdaus, 2015, 2016b, gender (Ariesta, 2014), persistensi (Fitlayeni, Marleni & Elvawati, 2015) hingga jaringannya (Firdaus, Ariesta, Rahayu, & Shalihin, 2019).…”
Section: Pendahuluanunclassified
“…Organizations play an important role in trade sector. (Fitlayeni, Rinel, Marleni, 2015) in their study on market traders found three roles of informal organizations, (1) strengthening the social network with fellow traders, (2) enhancing social network with buyers, and (3) improving solidarity.…”
Section: Street Vendors' Experience Of Being Chased Away By the Civil Service Police Unitmentioning
confidence: 99%